The Impact of Faith-Based Organizations on Schools and Families for Prevention of Bullying and Youth Violence - Groce, Jason L. (2019)
The lack of research regarding the potential relationship between the reduction of bullying through participation in faith-based organizations may have failed to expand available bullying intervention methods. Faith-based organizations could assist in reducing bullying via moral instruction, boundary-setting guidance, social engagement techniques, and understanding social engagement with the bully's parents. This study explored the relationship between bullying and involvement in faith-based activities through (a) discovering the association between the reduction of bullying incidence or inclinations and faith-based activities, and (b) identifying the mechanisms responsible for the suppression of bullying orientations and behaviors through faith-based activities. The theoretical construct of the study was Bronfenbrenner's ecological systems theory and its 5 level classification of diverse social contexts (i.e. microsystem, mesosystem, exosystem, macrosystem, and chronosystem). This theory was utilized in the creation of the central research questions of the study. The data for the questions was gathered through one-on-one interviews with (a) 11 adolescents, (b) 6 parents, and (c) 3 church officials. The interviews were transcribed, and codes and themes identified. The sample group for the research was ninth grade students enrolled at a school in the Midwest. The study found that parents felt more responsible for their influence on their child's attitude toward violence over faith-based activity. However, the organizations were also shown to be effective in contributing to strengthened social relationships and decreased bullying incidences. This study may contribute to social change by providing insight into bullying prevention and mitigation